EFEKTIFITAS PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - ., hanifah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The aim of this research is to improve the learning outcomes of Indonesian students in conversation text material through the application of the class I contextual Teaching and Learning (CTL) Approach in the second semester of the 2016-2017 academic year at SD Negeri Naleung Mass School, East Aceh Regency. The benefits of this research are to add new references and theories in the field of education, especially the implementation of classroom Action Research by applying various models or learning methods so as to improve student learning outcomes. To achieve this, the steps that need to be implemented are through the application of the Contextual Teaching and Learning (CTL) Approach. Data analysis methods used in this study uses descriptive analysis whose data is sourced from formative tests and classroom observations. This research was conducted in the increase in students mastery learning which reaches 85% classically. The results of the study show that in cycle I (one) the average value of students amounted to 64 and mastery learning reached 44%. These results indicate an improvement from the initial conditions with an average score of only 54.8 and a new learning completeness of 28%. While in cycle II (two) the average value of student was 79.2 and completeness of learning reached 92%. The conclusion of this study was the application of contextual Teaching and Learning (CTL) Approach to Indonesian learning. Conversational text material had a positive effect on improving learning outcomes in class I student semester II of the 2016-2017 school year at Nalueng Mass State Elementary School, East Aceh Regerency